xPIPE – Reception of DICOM Data from any Sender via the Internet - Czwoydzinski, J.; Eßeling, R.; Meier, N.; Heindel, W.; Lenzen, H. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: Various technologies have been established for DICOM data exchange in radiology. In addition to the patient CD, online transfers via VPN (virtual private network) or DICOM email are common practice. However, dedicated network solutions are generally not appropriate for data exchange with occasional and spontaneous partners due to missing infrastructure at the partner institutions and/or complex setup procedures. The purpose was to develop a practical solution to complement the established technologies to allow users worldwide to transfer images without registration.Materials and Methods: The development of the xPIPE system is based on Java and various software libraries. A client hosted on a website enables sending DICOM data to a receiving system of the hospital.Results: The new xPIPE system creates a gateway to a receiving hospital which is accessible from any point worldwide, giving other hospitals, clinics and patients a simple and secure method to transmit DICOM data without intermediate storage on external servers.Conclusion: The system was deployed at the University Hospital Münster and subsequently widely used even without information events and training. Data protection during transfer is ensured by the use of signatures and encryption. From the user’s perspective the system has only minor technical requirements and can be used with minimal setup effort.Key Points:• There is a need for DICOM receiving systems for connecting occasional and spontaneous partners.• A successful solution has to minimize the complexity for the partners.• The developed xPIPE system provides an option for simple and secure DICOM data transmission.• Availability of such receiver systems may reduce the risk of using insecure transmission paths.Citation Format:• Czwoydzinski J., Eßeling R., Meier N. et al. xPIPE – Reception of DICOM Data from any Sender via the Internet. Fortschr Röntgenstr 2015; 187: 380 – 384